Examining the impact of board gender diversity and regional differentiation in the ESG-corporate performance nexus : Evidence from financial service industry - Tran, Thu Huong; Lu, Wen Min; Ting, Irene Wei Kiong; Huang, Hsueh Li; Muhammad Ashraf, Fauzi (John Wiley and Sons Ltd, 2024)
This study explores the impact of environmental, social, and governance (ESG) factors on corporations by investigating how board gender diversity moderates the relationship between ESG practices and corporate performance across different regions. Using traditional data envelopment analysis (DEA) and chance-constrained DEA models, the study analyzes 225 financial service firms over an 11-year period (2011–2021). Results indicate that high (low) board gender diversity levels significantly influence the connection between the environmental (social) aspects of ESG practices and corporate performance. Thus, the roles of stakeholder engagement and regional distinctions are highlighted in achieving sustainable development goals.